Math, asked by Anonymous, 7 months ago

Simplify The Following: ​

Attachments:

Answers

Answered by ItzAritraKz22
2

Solution:-

To find:-

 \frac{ ( {\frac{3}{5}) }^{ - 7} }{ ( {\frac{3}{5}) }^{ - 5} }

By the Problem:-

 \frac{ ( {\frac{3}{5}) }^{ - 7} }{ ( {\frac{3}{5}) }^{ - 5} }  \\ =  >  ( {\frac{3}{5}) }^{( - 7) - ( - 5)}  \\  =  >( {\frac{3}{5}) }^{( - 7) + 5} \\   =  > ( {\frac{3}{5}) }^{ - 2}  \\  =  > ( {\frac{5}{3}) }^{  2} \\  or \\  =  >  \frac{25}{9}

Formula:-

 i) \: \frac{ {a}^{b} }{ {a}^{d} }   \\  =  >  {a}^{(b - d)}

ii) \:   ({\frac{1}{a} )}^{ - b}  \\  =  >  {a}^{b}

Answered by Anonymous
3

Answer:

HEYY HOW ARE YOU ☺☺☺☺✌✌✌✌✌

Similar questions